NATO of the Future: Less is More - DePorte, A. W. (Tufts Archival Research Center, 2005)
Volume 7, Issue 1. Winter In 1982 the Atlantic Alliance descended into one of its periodic tailspins of discord and mutual recrimination over issues ranging from trade to security to international development. Inevitably, questions have resurfaced about the future viability of the Alliance. Dr. A. W. DePorte addresses these questions in a restatement of the case for the Atlantic Alliance, arguing that its primary goals are being met and that the Alliance need not be threatened by occasional (and inevitable) disputes over non-central issues. Following a discussion of the various perceptions of what the Alliance should accomplish and how it has in fact responded, the author suggests that the Alliance will continue to perform very well if it is released from the burden of unwarranted expectations.